Social Pediatrics Training in Turkey - Emine Gülbin Gökçay; Bahar Kural; Gonca Keskindemirci; Olcay Neyzi (Çocuk Dergisi)
Training in Social Pediatrics at Medical Schools has deep roots in Turkey. Nowadays, there are Social Pediatrics divisions under the departments of child health and disease in many medical schools. Academicians in Social Pediatrics Divisions give lectures starting from the first year of medical education. Social Pediatrics is not a subspeciality yet in Turkey. There are universities with institutes providing postgraduate training in Social Pediatrics. This article aims to present the history and developments of training in Social Pediatrics in Turkey.